New diphenyl diselenides o-substituted by an O(S, Se)-caranyl skeleton – synthesis and application in asymmetric reactions. (6th June 2016) - Ścianowski, Jacek; Pacuła, Agata J.; Zielińska-Błajet, Mariola; Wojtczak, Andrzej
Abstract : A convenient methodology for the synthesis of optically active diselenides and selenides functionalized with terpenyl moieties and their applications in the selenenylation of alkenes, and Tsuji–Trost and Henry reactions are presented. Abstract : An efficient methodology for the synthesis of diphenyl diselenides o -substituted by O(S, Se)-caranyl moieties has been presented. 4-Caranyl and 4-isocaranyl groups have been connected to the phenyl ring by an oxygen, sulfur or selenium atom. The influence of the selenium–heteroatom interactions on the diastereoselectivity of the methoxyselenenylation of styrene has been evaluated. The best result was obtained for diselenide with an O-caranyl group substituted in the ortho -position. X-ray crystal structure of this compound was determined and the observed intramolecular interactions were discussed. Additionally diselenides bearing a sulfur atom were transformed to the corresponding methyl o -(S-caranyl) and o -(S-isocaranyl)-substituted phenyl selenides, and were tested as catalysts in the Tsuji–Trost allylic alkylation and Henry reaction.